Trends and Determinants of Job Search Intensity of Unemployed Females: Empirical Evidence from Egypt - Mowla, Somaya Ahmed Aly Abdel (Mediterranean Journal of Social Sciences, 2011)
The present study examines trends in unemployed females' job search intensity in Egypt in an important era of transitionaway from public sector employment guarantee. It examines determinants of job search intensity of unemployed females, modeling searchintensity as the total number of job search methods used by the unemployed. The empirical analysis is based on the Egyptian LaborMarket Surveys of 1998 and 2006. A comparative descriptive approach is used to analyze the difference between males' and females'search intensity. The study uses logistic regression analysis to examine the determinants of unemployed females' search intensity. Empiricalfindings suggest that the unemployed tend to search more intensively. However, this increase hides gender differences in search intensity.The gender gap in search intensity widened between 1998 and 2006. This gap is wider among youth than among all unemployedworkers. Examining determinants of females' search intensity reveals a significant effect of personal, household characteristics and labormarket conditions. The relationship between age and search intensity is inverted U-shaped. Education, previous work experience, andhousehold wealth have significant positive effects on search intensity. Females in labor markets where the unemployment rate is highersearch more intensively.